2019
DOI: 10.1111/dme.13895
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Type 2 diabetes in the UK

Abstract: Type 2 diabetes is a major UK public health priority. Among minority ethnic communities, the prevalence is alarmingly high, approximately three to five times higher than in the white British population. Particularly striking is the earlier onset of Type 2 diabetes, which occurs some 10–12 years younger, with a significant proportion of cases being diagnosed before the age of 40 years. This review focuses on the UK context and Type 2 diabetes in adult populations, exploring the available evidence regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 104 publications
(140 reference statements)
0
93
2
2
Order By: Relevance
“…Most studies undertaken have reported higher prevalence in BME groups for type 2 diabetes; however, like the 2004 HSfE, studies thus far have generally been modest in sample size, unable to adjust for important demographic factors and social deprivation, while only a few have used imputation techniques to adequately account for missing data. Some previously reported estimates suggest that prevalence is nearly 3-5 times higher in BME groups, 10 but our study highlights that when other demographic and socio-economic factors are accounted for, relative prevalence is unlikely to be as high as this. Nevertheless, our finding that the likelihood of diagnosis being over double that in Asian people and over 65% more likely in Black people still highlights major ethnic inequalities when compared with the White British population.…”
Section: Findings In Relation To Other Evidence and Implicationscontrasting
confidence: 63%
See 2 more Smart Citations
“…Most studies undertaken have reported higher prevalence in BME groups for type 2 diabetes; however, like the 2004 HSfE, studies thus far have generally been modest in sample size, unable to adjust for important demographic factors and social deprivation, while only a few have used imputation techniques to adequately account for missing data. Some previously reported estimates suggest that prevalence is nearly 3-5 times higher in BME groups, 10 but our study highlights that when other demographic and socio-economic factors are accounted for, relative prevalence is unlikely to be as high as this. Nevertheless, our finding that the likelihood of diagnosis being over double that in Asian people and over 65% more likely in Black people still highlights major ethnic inequalities when compared with the White British population.…”
Section: Findings In Relation To Other Evidence and Implicationscontrasting
confidence: 63%
“…[2][3][4][5][6][7][8][9] There is widespread acceptance that the prevalence of type 2 diabetes is indeed higher among Asian, Black and minority ethnic (BME) groups in the UK. 10 However, there are limited data available, and the last largescale survey was conducted in the early 2000s. The 2004 Health Survey for England (HSfE) collected data from around 13,500 adults and suggested that the prevalence of type 2 diabetes was much higher in Black Caribbean (9.5% men, 7.6% women), Indian (9.2% men, 5.9% women), Pakistani (7.3% men, 8.4% women), and Bangladeshi (8.0% men, 4.5% women) than in the general population (3.8% men, 3.1% women).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from differences in lifestyle and socioeconomic related parameters, these ethnic-related disparities in the T2DM prevalence are attributed to higher T2DM genetic predisposition and enhanced susceptibility for cardio-metabolic complications in relationship to body composition, central fat distribution and obesity [1,18,[68][69][70]. As such, significantly higher risk for insulin resistance and T2DM has been noted in South Asian, Chinese and Japanese individuals with overweight or obesity compared to weight-matched controls of Caucasian origin [68][69][70][71][72][73]. In Europe, several studies have investigated the prevalence of T2DM in migrant and ethnic minority groups compared to European host populations, with the accumulated evidence consistently showing higher T2DM prevalence among the former groups [68,[72][73][74][75][76][77][78][79].…”
Section: Diabetes Family Historymentioning
confidence: 99%
“…As such, significantly higher risk for insulin resistance and T2DM has been noted in South Asian, Chinese and Japanese individuals with overweight or obesity compared to weight-matched controls of Caucasian origin [68][69][70][71][72][73]. In Europe, several studies have investigated the prevalence of T2DM in migrant and ethnic minority groups compared to European host populations, with the accumulated evidence consistently showing higher T2DM prevalence among the former groups [68,[72][73][74][75][76][77][78][79]. For example, in the UK the T2DM prevalence among minority ethnic communities is approximately 3-to 5-fold higher than in the white British population, with earlier onset by 10-12 years and a significant proportion of T2DM patients aged less than 40 years [73].…”
Section: Diabetes Family Historymentioning
confidence: 99%